Public finance of Lithuania: Gender perspective - Rakauskienė, Ona Gražina; Chlivickas, Eugenijus (Journal of Business Economics and Management, 2007)
The paper presents the analysis of Lithuania’s economic growth, tax policy, state budget and municipality budgets, using of the EU structural funds support from a gender perspective. Gender asymmetry is examined not only at the microeconomic level, but also at the level of macroeconomics, therefore solutions of gender problems have to be relevant and adopted in view of macroeconomic criteria. First Published Online: 14 Oct 2010